2006
DOI: 10.1088/0957-0233/17/4/003
|View full text |Cite
|
Sign up to set email alerts
|

Measurement and modelling of dispersion characteristics of a two-mode birefringent holey fibre

Abstract: Employing several interferometric methods, we measured in a broad spectral range the wavelength dependences of the phase modal birefringence and the polarization mode dispersion for the LP01 and even LP11 spatial modes supported by a birefringent holey fibre. We also determined the wavelength dependence of the intermodal dispersion between the X- and Y-polarized LP01 and even LP11 spatial modes. Furthermore, using a full-vector finite-element method, we modelled all the measured dispersion characteristics and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 18 publications
0
11
0
Order By: Relevance
“…1 as lens 1 and lens 2) represented by a microscope objective (10×/0.30, Meopta), and an achromatic lens (74-ACR, Ocean Optics, Inc.). The fiber sample is pure silica holey fiber (PM-1550-01, Thorlabs) [17] of length z = (50650 ± 10) μm.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…1 as lens 1 and lens 2) represented by a microscope objective (10×/0.30, Meopta), and an achromatic lens (74-ACR, Ocean Optics, Inc.). The fiber sample is pure silica holey fiber (PM-1550-01, Thorlabs) [17] of length z = (50650 ± 10) μm.…”
Section: Methodsmentioning
confidence: 99%
“…To find the eigenpairs of the above equation, we used the Arnoldi method as an eigensolver and an unsymmetrical multifrontal method as a solver of linear system of equations. The calculations were carried out for the real geometry of the fiber [17]. The binary image of the fiber cross section shown in Fig.…”
Section: Numerical Modellingmentioning
confidence: 99%
“…Similarly, the ellipticalshape optical field indicated that the light was guided by the fiber core and the fundamental mode was supported. The orientation of the polarizer was along the longer or shorter axis of the elliptical core so that the group dispersion in the X or Y polarization [12] was measured.…”
Section: Resultsmentioning
confidence: 99%
“…We measured two different fibre samples. The first sample is pure silica holey fibre of length z = 50650 µm (PM-1550-01, Thorlabs, see its SEM photograph in [12]). The second sample is a rectangular-shape highly birefringent holey fibre of length z = 54200 µm made of SK222 optical glass with rectangular lattice and circular holes (see a similar fibre of IEMT with elliptical holes in [18]).…”
Section: Experimental Set-upsmentioning
confidence: 99%
See 1 more Smart Citation